Uma história do Grupo Escolar Farroupilha : sujeitos e práticas escolares (Farroupilha/RS, 1927-1949) - Fernandes, Cassiane Curtarelli (My University, 2016)
This thesis sought to research the educational background process of Farroupilha’s School Group, institution initially located in the district of Nova Vicenza (Caxias), later the city of Farroupilha/RS. The study was in 1927, when they are brought together two isolated state schools that existed in the district to form the Nova Vicenza’s Rural School Group, later called Farroupilha’s School Group, by the year of 1949, considering the range of school records found in Farroupilha’s State College Archive, old school group, about this period of time. To accomplish this narrative the theoretical and methodological assumptions of Cultural History guided the analysis, especially with the contributions of the historians Le Goff (1996), Ginzburg (2001, 2007), Chartier (1994, 2002, 2009), Burke (2008) and Pesavento (2008a, 2008b). The methodology consisted in the documental analysis of photographs and written documents such as enrollment books, pedagogical meetings books, civic celebrations books, books containing the history teacher, daily school book, among other sources located in the archive of Farroupilha’s State College (Farroupilha/RS). Moreover, it was consulted newspapers, reports, regulations and decrees in other archives, as well as oral statements made by other researchers. The produced study was divided into five chapters, beginning with the initial considerations, where it was specified the path build and the choices made during the research process. The second chapter aimed to understand the historical process of creation and implementation of Farroupilha’s School Group in Nova Vicenza’s context, then, the city of Farroupilha/RS, being possible to realize the experienced changes by this school in its early years of existence, as well as the production of a new school culture from the new building opened with the adoption of differentiated spaces, counting on the presence of other subjects, just like producing new school practices. The third and fourth chapter had premised attend to some constituent elements of the school culture of this institution, so in addition to weave a narrative about the school subjects, favoring students, teachers and directors, special attention was intended to the school practices produced in this space, throughout the 40s of the twentieth century, such as school festivities and the developed activities by the Agricultural School Club. Thus, it was found that through the action of "celebrate" this primary school "assumed" the role of internalizing patriotism, avoid forgetting the achievements of national and state history, as well as their heroes and symbols, in addition encouraging love and respect to the Mother Country, extolling the care and appreciation of the natural wealth for the country's progress, as well as emphasizing a prominently Brazilian culture at the expense of existing ethnic cultures. The result also point to the relevance that the Agricultural Club assumed in daily life of this school, since after a long period the rural education goes back again to be part of its educational background process, developing a social and educational work, approaching the knowledge of the school institution with the municipal context. In order to complete, it was introduced the final considerations which highlight the contribution of this narrative to the existing research in the field of history of school institutions at local, regional and national level, especially as regards the specific study of school groups.
Esta dissertação buscou pesquisar o processo histórico educacional do Grupo Escolar Farroupilha, instituição localizada inicialmente no distrito de Nova Vicenza (Caxias), posterior município de Farroupilha/RS. O trabalho teve como recorte temporal o ano de 1927, momento em que são reunidas duas escolas isoladas estaduais que existiam no distrito para a formação do Grupo Escolar Rural de Nova Vicenza, posteriormente denominado de Grupo Escolar Farroupilha, até o ano de 1949, levando-se em consideração a gama de registros escolares encontrados no Arquivo do Colégio Estadual Farroupilha, antigo grupo escolar, acerca deste período. Para realizar esta narrativa os pressupostos teórico-metodológicos da História Cultural orientaram a análise, sobretudo com as contribuições dos historiadores Le Goff (1996), Ginzburg (2001, 2007), Chartier (1994, 2002, 2009), Burke (2008) e Pesavento (2008a, 2008b). A metodologia empregada consistiu na análise documental de fotografias e documentos escritos como livros de matrículas, livros de reuniões pedagógicas, livros de comemorações cívicas, livros contendo o histórico dos professores, livro diário da escola, entre outras fontes localizadas no arquivo do Colégio Estadual Farroupilha (Farroupilha/RS). Além disso, foram consultados jornais, relatórios, regimentos e decretos em outros arquivos, assim como depoimentos orais realizados por outros pesquisadores. O estudo produzido foi divido em cinco capítulos, iniciando com as considerações iniciais, onde se especifica o percurso construído e as escolhas realizadas durante o processo de pesquisa. O segundo capítulo teve como propósito compreender o processo histórico de criação e de implantação do Grupo Escolar Farroupilha no contexto de Nova Vicenza e depois, do município de Farroupilha/RS, sendo possível perceber as mudanças vivenciadas por esta escola em seus primeiros anos de existência, assim como a produção de uma nova cultura escolar a partir da inauguração do novo prédio com a adoção de espaços diferenciados, contando com a presença de outros sujeitos, bem como produzindo novas práticas escolares. O terceiro e o quarto capítulo tiveram como premissa atentar para alguns elementos constitutivos da cultura escolar desta instituição, sendo assim, além de tecer uma narrativa acerca dos sujeitos escolares, privilegiando alunos (as), professoras e diretores (as), atenção especial foi destinada as práticas escolares produzidas neste espaço, ao longo da década de 40 do século XX, como as festividades escolares e as atividades desenvolvidas pelo Clube Agrícola Escolar. Deste modo, verificou-se que por meio da ação de “comemorar” esta escola primária “assumiu” a função de internalizar o patriotismo, evitar o esquecimento dos feitos da história nacional e estadual, bem como de seus heróis e símbolos, além de incentivar o amor e o respeito à Mãe Pátria, exaltando os cuidados e a valorização das riquezas naturais para o progresso do país, como também enfatizando uma cultura proeminentemente brasileira, em detrimento as culturas étnicas existentes. Os resultando também apontam para a relevância que o Clube Agrícola assumiu no cotidiano desta escola, uma vez que depois de um longo período o ensino rural volta novamente a fazer parte de seu processo histórico educacional, desenvolvendo ao que tudo indica um trabalho social e educativo, aproximando os saberes da instituição escolar com o contexto do município. Para concluir, são apresentadas as considerações finais, onde se destaca a contribuição desta narrativa para as pesquisas existentes no campo da história das instituições escolares em nível local, regional e nacional, especialmente no que refere ao estudo específico dos grupos escolares.
Keywords: Grupo Escolar Farroupilha - História; Escolas - História; Farroupilha (RS) - História; Scholl Group Farroupilha (Brazil) - History; Schools - History; Farroupilha (Brazil) - History